Rancang Bangun Modul Sistem Proteksi Kelistrikan pada Gedung Tower Airnav Unit Dekai - Saragih, Jovi Nandra; Koswara, Iwan; Juliarta, I Wayan (Universitas Batanghari Jambi, 2025)
This research aims to design and develop a microcontroller-based electrical protection system that is able to detect and handle voltage surges (overvoltage) and voltage drops (undervoltage) automatically. This system uses a PZEM-004T sensor, an Arduino Mega 2560 microcontroller as the main controller, and a Solid State Relay (SSR) to disconnect or connect the electric current according to the detected conditions. This research uses a User Trial test. The test was carried out by comparing the measurement results of the PZEM-004T sensor to a digital multimeter, showing an average difference of less than 3%, indicating good sensor accuracy. When the voltage exceeds 250V or drops below 190V, the SSR successfully disconnects the current with a response time of less than 0.5 seconds.